EARLY VS LATE CAFFEINE THERAPY IN PRETERM INFANTS: ANALYSIS OF CLINICAL OUTCOME - Niaz, Hafsa; Jalil, Jawad; Adil, Muhammad; Basheer, Faisal; Akhtar, Shahzad; Hamid, Naila (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study clinical outcome of early versus late caffeine therapy in preterm infants.Study Design: Prospective comparative study.Place and Duration of Study: Neonatal Intensive Care Unit, Pak Emirates Military Hospital, Rawalpindi, from Jan to Jul 2018.Methodology: A total of 40 preterm infants with gestational age